Pengembangan Buku Ajar untuk Mata Kuliah Pengembangan Bahan Ajar - Arista Ratih (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to describe developing a textbook for the Pengembangan Bahan Ajar subject and produce a valid textbook. The method used is development research using a 4D model (define, design, develop, and disseminate) with instruments in the form of a validity questionnaire in terms of the feasibility of content, language, graphics and presentation. The resulting product is a textbook. The results showed that the developed textbooks scored 84% with a valid category. In conclusion, the developed textbooks are valid and suitable to be used as a guide for students in Pengembangan Bahan Ajar subject. Keywords: Textbooks, Pengembangan Bahan Ajar Subject, Development Research